Mdivi-1 Protects Adult Rat Hippocampal Neural Stem Cells against Palmitate-Induced Oxidative Stress and Apoptosis - Kim, Sehee (Int J Mol Sci, 2017)
Palmitate concentrations in type 2 diabetic patients are higher than in healthy subjects. The prolonged elevation of plasma palmitate levels induces oxidative stress and mitochondrial dysfunction in neuronal cells. In this study, we examined the role of mdivi-1, a selective inhibitor of mitochondrial fission protein dynamin-regulated protein 1 (Drp1), on the survival of cultured hippocampal neural stem cells (NSCs) exposed to high palmitate. Treatment of hippocampal NSCs with mdivi-1 attenuated palmitate-induced increase in cell death and apoptosis. Palmitate exposure significantly increased Drp1 protein levels, which were prevented by pretreatment of cells with mdivi-1. We found that cytosolic Drp1 was translocated to the mitochondria when cells were exposed to palmitate. In contrast, palmitate-induced translocation of Drp1 was inhibited by mdivi-1 treatment. We also investigated mdivi-1 regulation of apoptosis at the mitochondrial level. Mdivi-1 rescued cells from palmitate-induced lipotoxicity by suppressing intracellular and mitochondrial reactive oxygen species production and stabilizing mitochondrial transmembrane potential. Mdivi-1-treated cells showed an increased Bcl-2/Bax ratio, prevention of cytochrome c release, and inhibition of caspase-3 activation. Our data suggest that mdivi-1 protects hippocampal NSCs against lipotoxicity-associated oxidative stress by preserving mitochondrial integrity and inhibiting mitochondrial apoptotic cascades.